Imaging the Met Receptor Tyrosine Kinase (Met) and Assessing Tumor Responses to a Met Tyrosine Kinase Inhibitor in Human Xenograft Mouse Models with a [99mTc] (AH-113018) or CY 5** (AH-112543) Labeled Peptide. Issue 9 (1st September 2015) - Jagoda, Elaine M.; Bhattacharyya, Sibaprasad; Kalen, Joseph; Riffle, Lisa; Leeder, Avrum; Histed, Stephanie; Williams, Mark; Wong, Karen J.; Xu, Biying; Szajek, Lawrence P.; Elbuluk, Osama; Cecchi, Fabiola; et al.
Developing an imaging agent targeting the hepatocyte growth factor receptor protein (Met) status of cancerous lesions would aid in the diagnosis and monitoring of Met-targeted tyrosine kinase inhibitors (TKIS). A peptide targeting Met labeled with [ 99m Tc] had high affinity in vitro (Kd = 3.3 nM) and detected relative changes in Met in human cancer cell lines. In vivo [ 99m Tc]-Met peptide (AH-113018) was retained in Met-expressing tumors, and high-expressing Met tumors (MKN-45) were easily visualized and quantitated using singlephoton emission computed tomography or optical imaging. In further studies, MKN-45 mouse xenografts treated with PHA 665752 (Met TKI) or vehicle were monitored weekly for tumor responses by [ 99m Tc]-Met peptide imaging and measurement of tumor volumes. Tumor uptake of [" m Tc]-Met peptide was significantly decreased as early as 1 week after PHA 665752 treatment, corresponding to decreases in tumor volumes. These results were comparable to Cy5**-Met peptide (AH-112543) fluorescence imaging using the same treatment model. [ 99m Tc] or Cy5**-Met peptide tumor uptake was further validated by histologic (necrosis, apoptosis) and immunoassay (total Met, p Met, and plasma shed Met) assessments in imaged and nonimaged cohorts. These data suggest that [ 99m Tc] or Cy5**-Met peptide imaging may have clinical diagnostic, prognostic, and therapeutic monitoring applications.